2013
DOI: 10.1109/tvcg.2013.89
|View full text |Cite
|
Sign up to set email alerts
|

The Five Ws for Information Visualization with Application to Healthcare Informatics

Abstract: The Five Ws is a popular concept for information gathering in journalistic reporting. It captures all aspects of a story or incidence: who, when, what, where, and why. We propose a framework composed of a suite of cooperating visual information displays to represent the Five Ws and demonstrate its use within a healthcare informatics application. Here, the who is the patient, the where is the patient's body, and the when, what, why is a reasoning chain which can be interactively sorted and brushed. The patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 30 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…One study reported training time of 6 minutes for its visualization, which used radial displays with a body map in the center of the radius and the relevant physiological parameters highlighted on the body map. 36 This was the shortest training time reported; the longest was a half hour. 30…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…One study reported training time of 6 minutes for its visualization, which used radial displays with a body map in the center of the radius and the relevant physiological parameters highlighted on the body map. 36 This was the shortest training time reported; the longest was a half hour. 30…”
Section: Resultsmentioning
confidence: 88%
“…Some of the articles describe systems for data visualization, for example, LifeLines2 and VISITORS. Others use visualization techniques such as sequential displays, 31 , 36 treemaps, 28 , 30 radial displays, 34 , 36 , 38 or icicle trees. 31…”
Section: Resultsmentioning
confidence: 99%
“…The visualization of knowledge is a field of study in its own right, and you may find it helpful to consult general works [ 39 , 40 ]. Although the visualization of data has become an active health informatics research area [ 41 , 42 ], the visualization of concepts is a very different order of activity.…”
Section: Resultsmentioning
confidence: 99%
“…As our domain case study is related to type 1 diabetes, we should point out the survey of electronic health record visualizations by Rind et al [42] and the five Ws for healthcare informatics visualization [65]. However, as SEQUENCE BRAIDING is a general-purpose event sequence and attribute visualization, we will not further detail less relevant domain visualizations.…”
Section: Temporal Event Sequence Visualizationmentioning
confidence: 99%